Cytokine Profile at Diagnosis Affecting Trough Concentration of Infliximab in Pediatric Crohn’s Disease - Yiyoung Kwon; Eun-Sil Kim; Yoon-Zi Kim; Yon-Ho Choe; Mi-Jin Kim (Biomedicines, 2022)
Background: This study aims to measure the concentration of cytokines produced during the inflammation process to investigate if there are any differences in response to treatment of pediatric Crohn’s disease and to determine if the initial tumor necrosis factor-alpha (TNF-α) level affected the trough concentration of infliximab (IFX). Methods: This study included 30 pediatric patients with moderate-to-severe Crohn’s disease. At the time of diagnosis, blood samples were collected for the measurement of cytokines (IL-6, TNF-α, IL-17A, and IL-10). Blood samples were extracted from patients who had begun IFX treatment to measure the IFX trough concentration immediately before the fourth dose administration. Results: All cytokines (TNF-α, IL-6, IL-10, and IL-17A) were significantly higher in patients who did not achieve clinical or biochemical remission than in those who did (p = 0.027, 0.006, 0.017, 0.032, respectively). TNF-α had a negative correlation with the IFX trough concentration (Pearson coefficient = −0.425, p = 0.034). The diagnostic capability of the initial TNF-α concentration to predict under the therapeutic IFX trough concentration, defined as less than 3 µg/mL, had an area under the receiver operating characteristic of 0.730 (p = 0.049). The TNF-α concentration was set at 27.6 pg/mL as the cutoff value. Conclusions: Measuring cytokines at the time of diagnosis can be used to predict the treatment response. Measuring the initial TNF-α concentration may help to predict the treatment response to IFX. When the initial TNF-α concentration is greater than 27.6 pg/mL, a higher dose of IFX may be more appropriate than routinely administering 5 mg/kg of IFX to maintain the therapeutic concentration.